Receiving the news of a diagnosis of motor neuron disease: What does it take to make it better? - Aoun, Samar; Breen, Lauren; Howting, Denise; Edis, R.; Oliver, D.; Henderson, R.; O'connor, M.; Harris, R.; Birks, C. (2015)
Our objectives were to identify the experiences of people with MND in receiving the diagnosis and to determine which aspects of breaking this bad news were associated with greater satisfaction with the way the diagnosis was delivered to them. An anonymous postal survey was facilitated by all MND associations in Australia, in 2014, and centred on the SPIKES protocol for communicating bad news. Of the patients (n?=?248, response rate 29%), 36% were dissatisfied with the delivery of the diagnosis and gave low ratings on the ability/skills of their neurologists to deliver the diagnosis. It was evident that the longer the patients spent with their neurologists during breaking such bad news, the more they were satisfied and the higher they rated the neurologists’ abilities/skills. The largest significant differences between neurologists rated as having high or low skills in delivering the diagnosis were in four domains: 1) responding empathically to the feelings of patient/family; 2) sharing the information and suggesting realistic goals; 3) exploring what patient/family are expecting or hoping for; and 4) making a plan and following through. In conclusion, with over one-third of patients dissatisfied with their experience, there is room for improvement in the practice of neurologists in specified areas that could form the basis for changing practice, and the development of standards and protocols likely to have implications at the international level.